Scientific projects and technological scientific literacy of students in Peruvian public educational institutions - Chávez, Alicia (2023)
This academic work allows us to reflect on the relevance of research and innovation strategies that students use in science subjects, where students respond to academic activities using their instincts or simply by empirical experiences; However, it is necessary that to consolidate their learning, they have the ability to seek information and publicize their critical position, to achieve the scientific knowledge that respond to the problem posed. Therefore, the objective is to base the contributions of strategies such as school scientific projects and the need for students to attend public educational institutions have adequate technological scientific literacy, necessary to develop their ability to inquiry and deduction demonstrating research culture. The methodology used is based on the search and analysis of various documentary sources, of institutions that provide relevant contributions, such as the Ministry of Education, Concytec, INEI among others. This study allows you to inquire about strategies in the science area, creating spaces for meaningful learning, and thus develop logical principles of inquiry, research skills and scientific skills in students.